The Application of Rice Hull Mulch and Potassium Nitrate on Growth and Yield of Kailan (Brassica oleraceae var. Long Leaf) - Sri Ramadiana (UNIVERSITY OF LAMPUNG, 2011)
Potassium (K) is absorbed by plants in larger amounts than any other mineral element except N to optimalize plant growth. Mulches may be influenced an available K at vegetative growth phase of plant. The research was conducted in Simpang Kanan Village, Gisting, Tanggamus Lampung Province. The objectives of this research were to study the application of KNO3 and rice hull mulch on growth and yield of kailan. Fields experiments were arranged by a factorial in a completely randomized block design with 10 treatments and 3 replications. A first factor was (1) dosages of KNO3 (150, 175, 200, 225, and 250 kg ha-1) and the second factor was mulch of the rice hull (with and without the rice hull). The results showed that the application of the rice hull did not significantly affected the yield of kailan, however the application of KNO3 till 250 kg ha-1 increased the level of greenness up to 6.10% and the wide of leaf up to 18,57%. In addition, the present of potassium fertilizer suspended with the rice hull significantly affected the width of kalian leaf.Keywords: Kailan, mulch, potassium nitrate, rice hull